Performance evaluation of petrochemical wastewater fed air-cathode microbial fuel cells using yeast biocatalyst - Sumaya, Sarmin; Asmida, Ideris; Chin, S. Y.; Cheng, C. K.; Khan, Maksudur R. (Universiti Malaysia Pahang, 2018)
This paper presents the performance of air-cathode microbial fuel cell (AC-MFC) treating the petrochemical wastewater (PCW) from acrylic acid plant. The wastewater which is typically incinerated and possesses very high chemical oxygen demand (COD) due to presence of acrylic acid along with other organic acids. The goal of the present study is to evaluate the viability of treating the wastewater using yeast (Saccharomyces cerevisiae) as biocatalyst in AC-MFC for simultaneous treatment of wastewater and electricity generation. This study demonstrates that Saccharomyces cerevisiae could function as a good biocatalyst producing high power density of 0.24 W/m3 using PCW with an initial COD of 26,000 mg/L. The COD removal efficiency and the columbic efficiency (CE) were found as 38% and 23.6% respectively. The electron transfer process across the electrode/biofilm/solution interface was analyzed by electrochemical impedance spectroscopy (EIS). The present work demonstrates the potential of MFC for the treatment of acrylic acid plant PCW using Saccharomyces cerevisiae as biocatalyst.